POJĘCIE INTERESU SPOŁECZNEGO JAKO PRZESŁANKI UDZIAŁU PROKURATORA W POSTĘPOWANIU - Matusiak, Anna (Zeszyty Prawnicze, 2016)
THE CONCEPT OF PUBLIC INTEREST AS GROUNDS FOR A PROSECUTOR’S PARTICIPATION IN PROCEEDINGS Summary The term “public interest” is often treated as the equivalent of “social interest,” which is a concept derived from colloquial language. It is a common expression in the social sciences, mainly in sociology, political science, psychology and economics. However, it is certainly used in the various branches and disciplines of law. It became a legal concept as soon as it appeared in the texts of normative acts. For many years a discussion has been going on in the literature whether the concept of “public interest” does not in fact belong primarily to the political sphere, which would mean that lawyers should refrain from using it in their analyses. However, it is hard to agree with this hypothesis. The fact that the expression appears in a number of acts implies that for the rational legislator it is associated with specific values and objectives. Regardless of whether or not the interchangeability of the terms “public interest” and “social interest” is due to a lack of precision or to the fact that the difference between them is relatively small, terminology should be used accurately. Since the rational legislator uses them as different expressions, they should not be considered to have the same meaning. Public interest is not synonymous with the concept of social interest. Terminological analysis leads to the conclusion that the differences may not be fundamental, nevertheless they do exist and a precise use of the terminology is required.